2015
DOI: 10.1891/1946-6560.6.2.217
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Behaviors as a Predictor of Partner Violence Among Heterosexual Female and Male Adolescents

Abstract: This study investigates the prevalence of adolescent intimate partner violence (IPV) perpetration, IPV victimization, and controlling behaviors among 486 heterosexual high school students. Participants completed surveys that measured three types of IPV victimization (sexual, physical, and psychological) and two types of controlling behaviors (intimidation and threats). Results reveal high prevalence of dating violence in youth: 46% emotional violence, 34% physical violence, and 16% sexual violence. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
2
17
1
1
Order By: Relevance
“…Interestingly, although the well documented concurrent association between physical and psychological aggression was observed (Bates et al, 2014;Bookwala et al, 1992;Burman et al, 1992;Carney & Barner, 2012;Cordova et al, 1993;Fawson, 2015;Lloyd, 1996;Margolin et al, 1988;O'Leary & Slep, 2003;Sabourin et al, 1993), we found no support for the conclusion that earlier physical aggression contributed to the emergence of later psychological aggression.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, although the well documented concurrent association between physical and psychological aggression was observed (Bates et al, 2014;Bookwala et al, 1992;Burman et al, 1992;Carney & Barner, 2012;Cordova et al, 1993;Fawson, 2015;Lloyd, 1996;Margolin et al, 1988;O'Leary & Slep, 2003;Sabourin et al, 1993), we found no support for the conclusion that earlier physical aggression contributed to the emergence of later psychological aggression.…”
Section: Discussioncontrasting
confidence: 93%
“…Our central findings of an apparent temporal pattern between psychological and physical aggression takes nothing away from the well documented stability for both forms of aggression and their moderate-to-strong concurrent relationships. Indeed, these are consistent with the existing literature which has documented stability and concurrent associations during adolescence (Cano et al, 1998;Fawson, 2015;Fritz & Slep, 2009;O'Leary & Slep, 2003) and adulthood (Aldarondo, 1996;Bates et al, 2014;Bookwala et al, 1992;Capaldi et al, 2003;Carney & Barner, 2012;Fritz & O'Leary, 2004;Hamby & Sugarman, 1999;Lorber & O'Leary, 2004;Woffordt et al, 1994). Our study shows these associations across multiple time points among young adults, suggesting that these associations continue over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Analyses focused on determining correlates of CBs revealed that young women, and women who have resided outside of Spain, are at greatest risk of experiencing control within the context of an ongoing relationship. These findings align with recent research which indicated that the highest prevalence of CBs was among adolescents ( M age = 15.7; Fawson, 2015). That women who are not lifelong residents of Spain are at greater risk suggests a potential link between immigrant status and IPV, which may be a function of social isolation and a more limited social network observed among immigrant women (Rodríguez-Menés & Safranoff, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…De un lado, las relaciones, aunque estadísticamente significativas, son de una magnitud pequeña y de modo tentativo se podrían inferir que las actitudes transcendentes se encuentran ligadas a una mayor sensibilidad personal, mientras que las sexistas más estrechamente vinculadas la insensibilidad social. Por otro lado, las diferencias a nivel de género pueden referirse en torno a la dureza emocional, interpretando que los varones suelen adscribirse con ello al rol de agresores y las mujeres al de víctima (Fawson, 2015;Herrero, Torres, Fernández-Suárez, y Rodríguez-Díaz, 2016).…”
Section: Tabla 4 Correlaciones Entre Las Dimensiones Del Earg/gras Y unclassified